Analyzing the impact factors of customer loyalty among small and medium-sized hotels in Dubai - Al Balushi, Abdullah Ali Mohammed (2023)
This research aims to identify the most important factors that contribute to customer loyalty in the hotel sector, specifically in Dubai's hotels. Small and medium-sized hotels (SMSHs) were examined from the standpoint of their customers using customer loyalty as a performance metric. This research shed additional light on how customer satisfaction and trust in SMSHs contribute to customer loyalty, particularly within Dubai's hotel sector SMSHs. A quantitative research involves the data was analysed using Smart-PLS based on a sample random of 384 respondents from SMSHs in Dubai. The findings showed a positive and significant relationship between customer trust, service quality, customer satisfaction and customer loyalty in the SMSHs in Dubai. Also, customer satisfaction mediates the relationship between customer trust and customer loyalty, and customer satisfaction mediates the relationship between customer trust and customer loyalty in the SMSHs in Dubai. To boost client satisfaction, hotels should undertake a more detailed service assessment of online hotel performance and improve the hotel's application system, which is prone to faults, by speeding up digital technology. An original research on small and medium-sized hotels in Dubai would provide valuable insights into the unique challenges and opportunities faced by this segment of the hospitality industry in a highly competitive and dynamic market.